Load frequency regulation for multi-area power systems with renewable sources via active disturbance rejection control. (August 2022) - Wu, Zhenlong; Liu, Yanhong; Chen, YangQuan; Li, Donghai; Li, Bingnan; Zhu, Feng
Abstract: The stability and reliability of the power grid are facing great challenges caused by the intermittency and randomness of renewable energy, for example, the frequency variations induced by the load variance. To handle these challenges, the load frequency regulation is becoming a powerful feasible alternative. This paper focuses on the load frequency regulation for multi-area power systems with renewable sources via a cascaded active disturbance rejection control (ADRC) approach. By introducing a multi-area power system with renewable sources, a cascaded ADRC structure is structured for a multi-area power system, which contains a photovoltaic system, a thermal system and a wind system. Based on the ADRC principle and the parameter stability region, a practical and effective design procedure for the proposed cascaded ADRC is provided. Simulations illustrate that the proposed cascaded ADRC can ensure the stronger ability to reject the consumed power compared with other comparative control strategies under different scenarios. Besides, it needs the shortest time to return to the stable state with the smallest overshoot under all operating conditions when the load variance occurs. The successful application of the multi-area power system indicates a promising potential of the proposed cascaded ADRC in the power industry.